Induction of labor versus expectant management for pregnancies beyond 41 weeks. (20th June 2013) - Daskalakis, George; Zacharakis, Dimitrios; Simou, Maria; Pappa, Peny; Detorakis, Stelios; Mesogitis, Spyros; Antsaklis, Aris
Abstract: Objective : To compare the outcome following labor induction at 41 + 1 weeks of gestation and after expectant management and selective induction at 42 completed weeks. Method : A retrospective analysis of post-term pregnancies in a 2-year period. In the induction group, women at 41 + 1 weeks of gestation received 3 mg prostaglandin E2 (dinoprostone) in the posterior fornix, repeating the dose 6 h later. Women with a Bishop score >6 had artificial rupture of the membranes. In the expectant management group, women at more than 41 weeks gestation were checked every 2 days in the hospital. In case of abnormalities either in the fetal heart rate evaluation or in the biophysical profile, labor was induced. Labor was also induced in all cases that pregnancy exceeded 42 + 1 gestational weeks. Results : A total of 438 women who met the inclusion criteria were included in the study. In all, 211 comprised the induction group, while the expectant management group consisted of 227 women. The cesarean delivery rate in the induction group was 36.5% compared to 34.4% in the expectant management group, whereas the operative vaginal delivery rate was 11.4 and 9.2% in the two groups, respectively. The vast majority of women in the expectant management group (74%) had a spontaneous onset of labor. Conclusion : The perinatal outcome does not differ following a policy of routine labor induction in comparison to expectant management in pregnancies beyond 41 weeks.